Benralizumab improves symptoms of patients with severe, eosinophilic asthma with a diagnosis of nasal polyposis. Issue 1 (8th June 2021) - Canonica, Giorgio Walter; Harrison, Tim W.; Chanez, Pascal; Menzella, Francesco; Louis, Renaud; Cosio, Borja G.; Lugogo, Njira L.; Mohan, Arjun; Burden, Annie; Garcia Gil, Esther
Abstract: Background: Clinically meaningful improvement in the Sino‐Nasal Outcome Test‐22 (SNOT‐22) was observed in patients with severe, eosinophilic asthma, and nasal polyposis (NP) treated with benralizumab in the ANDHI trial. A post hoc assessment of the effects of benralizumab on SNOT‐22 response and asthma efficacy measures in these patients was conducted for further characterization of the efficacy and safety of benralizumab for patients with severe asthma and NP. Methods: Adults with severe, eosinophilic asthma who had experienced ≥2 prior‐year exacerbations despite high‐dosage inhaled corticosteroid plus additional controller[s] were randomized to 24 weeks of benralizumab or placebo. Patients with physician‐diagnosed chronic rhinosinusitis with NP of any severity ongoing at baseline who consented to participate were included in the current ANDHI NP substudy population. Effect on NP symptoms was assessed by the SNOT‐22, with an improvement of at least 8.9 defined as clinically significant (responder). Effects on chronic asthma outcomes were assessed by means of annualized asthma exacerbation rate (AER), St. George's Respiratory Questionnaire (SGRQ) total score, forced expiratory volume in one second (FEV1 ), and Asthma Control Questionnaire‐6 (ACQ‐6). All p ‐values were nominal. Results: Of the ANDHI population ( n  = 656), 23% ( n  = 153) participated in the NP substudy ( n  = 96 benralizumab; n  = 57 placebo). Patients were 50% female, with mean age of 53 years, had prior‐year AER = 3.3; mean pre‐bronchodilator FEV1  = 55% predicted; and median blood eosinophil count ​= 510 cells/µl. For patients with high baseline SNOT‐22 scores (>30), benralizumab treatment improved symptoms of NP as measured by SNOT‐22 from baseline to Week 24 compared with placebo (Week 24: −10.44 [ p  = .0176]). Percentage of responders to SNOT‐22 was greater for benralizumab vs. placebo (71.3% vs. 45.5%; p  = .0036), and effect was enhanced for patients with high baseline SNOT‐22 scores (>30). A 69% reduction vs. placebo in annualized AER (0.77 vs. 2.47; p  < .0001) and greater clinically meaningful improvements from baseline in SGRQ total score (−16.7), FEV1 (+0.32 L), and ACQ‐6 (–0.88) were observed ( p  < .0001). Benralizumab was well‐tolerated. Frequency of adverse events (AEs) was similar for benralizumab (76.0%) and placebo (73.7%) groups. Most common AEs (frequency ≥5%) reported at a greater frequency in benralizumab vs. placebo included headache, sinusitis, pyrexia, and influenza. Conclusions: These substudy data from ANDHI demonstrated the efficacy profile of benralizumab for patients with severe, eosinophilic asthma and NP, with improvement in SNOT‐22 and asthma outcomes. Abstract : The combination of asthma and nasal polyposis provides significant treatment challenges and substantial disease burden, including a greater number of asthma exacerbations annually, which negatively impacts quality of life. Clinically meaningful improvement in the SNOT‐22 was observed early and maintained over time for patients with severe, eosinophilic asthma and nasal polyposis treated with benralizumab in the ANDHI trial. This ANDHI substudy demonstrated that benralizumab is safe and efficacious for patients with severe, eosinophilic asthma and nasal polyposis, with improvement in SNOT‐22 total scores and asthma outcomes. Abbreviation: ACQ‐6, Asthma Control Questionnaire‐6; AER, asthma exacerbation rate; CRSwNP, chronic rhinosinusitis with nasal polyposis; FEV1, forced expiratory volume in 1 second; SGRQ, St. George's Respiratory Questionnaire; SNOT‐22, Sino‐Nasal Outcome Test